Desinfeksi Hasil Cetakan - Sumadhi Sastrodihardjo (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2016)
Impression taking is performed to find model of patient’s teeth and oral cavity in making restoration or orthodontic appliances. The impression enable bacteria, fungi or virus from saliva or blood in oral cavity to be transferred. Washing the impression by using running water is not enough to completely remove all of bacteria, fungi or virus has been attached on the impression. Therefore the disinfection procedure on impression is needed to avoid the cross infection between the patient and operator. Cross infection of contamination of virus, fungi or bacteria cause of B hepatitis, tuberculosis, herpes zoster and Human Immunodeficiency Virus-Acquired Immune Deficiency Syndrome (HIV-AIDS) diseases. There are many many disinfectant agents which have been recommended to be used in effort to disinfect impression such as chlorine compound, iodophore, glutaraldehide and phenol. There are several methods of disinfection can be performed such as immersion, spray or admix the disinfectant into impression material. However several disinfection methods cause side effects such as dimensional change especially on alginate impression, quality of impression surface, surface roughness and other properties of impression material. In this paper the side effects occur in impression material caused by impression disinfection will be studied and discussed. Farther the disinfection by using UV light, blue light, microwave, autoclave, gargle and the possibility of traditional flora solution using as disinfectant of impression will be explained.